ANALYZING STUDENTS’ NEEDS ON READING TEXT MATERIAL AT VOCATIONAL HIGH SCHOOL - Titin Suhartini Kaaba; Iin Apriliyani Pauba (SALEE: Study of Applied Linguistics and English Education, 2020)
Abstract The objective of this research is to analyze the needs of students in reading text material in SMK Technology Muhammadiyah at Health Analisis Department. This research was conducted in class X majoring in Health Analisis in SMK Technology Muhammadiyah. The type of research method used was qualitative with a total number of participants of twenty people. The data was collected through questionnaires and open-ended interviews. The data was then analyzed using descriptive qualitative techniques that consist of 1) data preparation, 2) all data reading, 3) process of coding, 4) carefully description, 5) narrative approach, 6) data presentation. The results of this study indicate that there are three things needed to be achived by students of SMK Technology Muhammadiyah they are: 1) Necessity about reading material on the topics of health terms, medical devices. 2) Lacks in the form of material incompatibility taught with material needed by the students. 3) Wants covering material that students want to learn and that never been taught. The implication from this research is that students can achieve learning goals based on the material they need. Keywords: reading text material, students’ need analysis